2018
DOI: 10.1038/s41598-018-29060-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Loading and Tendon Healing Affect Multiscale Tendon Properties and ECM Stress Transmission

Abstract: The extracellular matrix (ECM) is the primary biomechanical environment that interacts with tendon cells (tenocytes). Stresses applied via muscle contraction during skeletal movement transfer across structural hierarchies to the tenocyte nucleus in native uninjured tendons. Alterations to ECM structural and mechanical properties due to mechanical loading and tissue healing may affect this multiscale strain transfer and stress transmission through the ECM. This study explores the interface between dynamic loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 71 publications
2
56
0
Order By: Relevance
“…Previously, we demonstrated that fatigue loading increased the crimp amplitude across the tendon width and length, and these structural alterations were shown to be both region and load dependent . Later work discovered that fatigue loading negatively altered tendon macroscale mechanical and structural properties . At the microscale, fatigue loading abrogated collagen and nuclear reorganization with applied strain, leading to reduced nuclear strain transfer and deficits in ECM stress transmission .…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Previously, we demonstrated that fatigue loading increased the crimp amplitude across the tendon width and length, and these structural alterations were shown to be both region and load dependent . Later work discovered that fatigue loading negatively altered tendon macroscale mechanical and structural properties . At the microscale, fatigue loading abrogated collagen and nuclear reorganization with applied strain, leading to reduced nuclear strain transfer and deficits in ECM stress transmission .…”
Section: Discussionmentioning
confidence: 89%
“…Tendons are known to become more prone to injury and rupture during aging, yet, the biomechanical underpinning of this clinical presentation remains poorly understood . The ability of tendon to maintain homeostasis following fatigue loading may be affected by restoration of native multiscale strain transfer mechanisms . The differential mechanical and structural response between tendon type and age to fatigue loading may therefore have important implications for multiscale strain transfer and ECM stress transmission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations